The effect of high iron doses (fe2+) on the growth of broccoli plants (brassica oleracea var. italica) (2014)
Tests were carried out under greenhouse conditions in Tunja (Colombia) in order to evaluate the effect of Fe2+ toxicity on the growth of broccoli plants. ‘Legacy’ hybrid Brassica oleracea var. Italica plantlets were grown in glass containers with a nutritive solution. Iron sulfate was added to the substrate in order to produce excess iron at concentrations of 100 and 200 mg L-1; a control without iron sulfate applications was used. The following evaluations were made: leaf area, total dry weight of the plants, distribution of dry mass (DM) in the different organs, absolute growth rate, relative growth rate, net assimilation rate and the root:shoot ratio. The total DM decreased drastically in the plants subjected to excess Fe2+, the growth indices progressively decreased with increases in the Fe2+ concentrations in the substrate and the distribution of DM in the organs varied as a function of the needs of the plants, with 15.85 and 11.10% less DM in the roots of the plants subjected to Fe2+ than in the control plants, at 100 and 250 mg L-1, respectively.